2011
DOI: 10.1161/circresaha.110.233924
|View full text |Cite
|
Sign up to set email alerts
|

The ShcA Phosphotyrosine Docking Protein Uses Distinct Mechanisms to Regulate Myocyte and Global Heart Function

Abstract: Rationale Although tyrosine kinases (TKs) are important for cardiac function, their relevant downstream targets in the adult heart are unknown. The ShcA docking protein binds specific phosphotyrosine (pTyr) sites on activated TKs through its N-terminal pTyr-binding (PTB) and C-terminal SH2 domains and stimulates downstream pathways through motifs such as pTyr sites in its central CH1 region. Therefore, ShcA could be a potential hub for downstream TK signaling in the myocardium. Objective To define the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
(69 reference statements)
0
20
0
Order By: Relevance
“…Application of shear stress to endothelial cells, for instance, induces the association of all three Shc isoforms with ␤ 1 and ␣ v ␤ 3 integrins, and abnormal shear patterns in mouse vasculature stimulate Shc translocation to junctional mechanosensory complexes (34,35). Conditional deletion of all Shc isoforms in cardiomyocytes leads to impaired mechanical coupling, and knock-in mutants of Shc prevent the formation of muscle spindles, mechanosensory organs within skeletal muscle (36,37). In this study, we link Shc with tension-induced RhoA activity, providing a potential mechanism for such observations and for multiple cellular processes related to RhoAlinked force transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Application of shear stress to endothelial cells, for instance, induces the association of all three Shc isoforms with ␤ 1 and ␣ v ␤ 3 integrins, and abnormal shear patterns in mouse vasculature stimulate Shc translocation to junctional mechanosensory complexes (34,35). Conditional deletion of all Shc isoforms in cardiomyocytes leads to impaired mechanical coupling, and knock-in mutants of Shc prevent the formation of muscle spindles, mechanosensory organs within skeletal muscle (36,37). In this study, we link Shc with tension-induced RhoA activity, providing a potential mechanism for such observations and for multiple cellular processes related to RhoAlinked force transduction.…”
Section: Discussionmentioning
confidence: 99%
“…More detailed gene-targeting work has shown that the expression of the PTB domain of Shc specifically in cardiomyocytes is critical for midgestational heart development and embryonic life. 11 Conditional knockout strategies have shown that Shc is also important for the proper development/function of other organs such as skeletal muscle, 11 brain, 12 cardiomyocytes, 13 and thymocytes, 14 because tissue-specific deletion of Shc resulted in living but underdeveloped mice. To address the role of Shc in angiogenesis in vivo, we studied loss of Shc function using morpholino (MO) antisense technology in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…These events lead to the activation of the Erk/mitogen-activated protein kinase pathway and cell proliferation (5,8). Germline deletion of ShcA in mice leads to profound embryonic cardiovascular defects (9), whereas deletion of ShcA in cardiomyocytes after birth induces a moderately impaired systolic function (10). Thus, ShcA plays a crucial role during heart development, but the underlying molecular mechanisms are largely unknown.…”
mentioning
confidence: 99%